Pengenalan Dunia Pertanian Berkelanjutan pada Siswa-Siswi SD Negeri Cermee 4 Kabupaten Bondowoso - Muhammad Nurdika Putra; Muhammad Iqbal; Quinta Zerlina Maida; Izzat Braga Arzeta; Aurora Majesta Nindya Chairiva; Febryan Ali Kusuma; Oria Alit Farisi; Hasbi Mubarak Su’ud; Agung Nugroho Puspito (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2026)
Environmental education plays a strategic role in addressing the declining interest of younger generations in agriculture and the lack of knowledge among students in agrarian areas, as observed at SD Negeri Cermee 4, Bondowoso. The purpose of the social project was to increase basic knowledge and instill environmental care and responsibility through sustainable agriculture introduction. The activity was conducted for 10 weeks at SD Negeri Cermee 4, involving 15 students from grades 4 and 5, using a combined method of material presentation, hands-on vegetable planting (mustard greens and spinach), educational quizzes, and post-activity monitoring. Results showed a significant increase in student knowledge of 80–85% and high participation levels. The project proved effective in fostering responsibility, perseverance, practical skills, and environmental awareness, thus playing a role in developing future generations essential for national food security.